1999
DOI: 10.1902/jop.1999.70.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease in Patients With cleft Palate and Patients With Unilateral and Bilateral Clefts of Lip, Palate, and Alveolus

Abstract: A critical periodontal situation was found in patients with unilateral and bilateral cleft lip, palate, and alveolus, ultimately leading to tooth loss in the front tooth region. In contrast, patients with cleft palate exhibited periodontal situations similar to that found in the general population with additional damage, which may be attributed to orthodontic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
46
0
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 23 publications
9
46
0
14
Order By: Relevance
“…This may be the reason for the low SBI score in Group II patients. These results were in accordance to the study performed by Alexander et al .,[8] and Schultes et al . [6] The presence of cleft, which hampered brushing efficiency, especially in both quadrants of the maxillary arch, resulted in more accumulation of plaque.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This may be the reason for the low SBI score in Group II patients. These results were in accordance to the study performed by Alexander et al .,[8] and Schultes et al . [6] The presence of cleft, which hampered brushing efficiency, especially in both quadrants of the maxillary arch, resulted in more accumulation of plaque.…”
Section: Discussionsupporting
confidence: 94%
“…A considerable improvement in periodontal health can be achieved by secondary osteoplastic surgery. [8]…”
Section: Introductionmentioning
confidence: 99%
“…3,10,[18][19][20] Several studies of periodontal disease progression reported increased pocket depths, attachment loss, and gingival inflammation at the cleft region versus controls. 2,4,8,16,21 Gaggl et al 7 analyzed several types of cleft, including UCLP, CP, and bilateral CLAP. Patients with UCLP and bilateral CLAP showed a greater number of periodontal lesions in the maxillary front tooth region compared with the general population.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Another possible reason is poorly developed osseous structures. 7,8 The few studies that have analyzed the periodontal status of these persons showed a high incidence of plaque and bleeding on probing and a high level of periodontal attachment loss. 8,9 In osseous clefts, the osseous structures are absent or poorly developed in the region of periodontal supportive tissues.…”
Section: Introductionmentioning
confidence: 99%
“…2 Poorly developed or absent osseous structures in periodontal supportive tissues are widely seen in osseous clefts. 3 Children affected by CLP have several problems, caused by anodontia, tooth malformation, and a deficiency of soft and hard tissue in the cleft region. 4,5 Reductions in bone levels in the areas adjacent to the cleft region are associated with delayed tooth formation and eruption, anatomical defects, and problems with orthodontic movement.…”
Section: Introductionmentioning
confidence: 99%